Retention of thallium(I) on goethite, hematite, and manganite: Quantitative insights and mechanistic study. (1st August 2022) - Chen, Wanpeng; Huangfu, Xiaoliu; Xiong, Jiaming; Liu, Juchao; Wang, Hainan; Yao, Jinni; Liu, Hongxia; He, Qiang; Ma, Jun; Liu, Caihong; Chen, Yao
Highlights: Increasing pH enhances the retention of Tl(I) on iron/manganese (hydr)oxides. The properties of Tl(I) binding species affects the retention and release of Tl(I). The hydration of surface hydroxyl groups dominates the sustained retention of Tl(I). The binding response of alkaline species MeOTlOH − is faster than neutral MeOHTl + . Higher adsorption energy of alkaline Tl(I) species drives the rapid retention. Abstract: The reversibility of monovalent thallium (Tl) absorption on widely distributed iron/manganese secondary minerals may affect environmental Tl migration and global cycling. Nevertheless, quantitative and mechanistic studies on the interfacial retention and release reactions involving Tl(I) are limited. In this study, batch and stirred-flow experiments, unified kinetics modeling, spectral detection, and theoretical calculations were used to elucidate the retention behaviors of Tl(I) on goethite, hematite, and manganite with different solution pH values and Tl loading concentrations. Sustained Tl(I) retention ( k d, MeOHTl =0.005∼0.018 min −1 ) was induced by hydration of the surface hydroxyl groups. Rapid Tl(I) retention ( k d, MeOTlOH =1.232∼2.917 min −1 ) was enhanced by the abundant hydroxide ions and deprotonated hydroxyl groups, which increased the Tl(I) binding ability. Compared to the ambient Tl concentration, pH had a more substantial effect on the formation and distribution of surface Tl(I) binding species. In alkaline environments, the large adsorption energy for Tl(I) binding to surface species ( E ads =-6.14 eV) induced fast Tl(I) binding response on the surfaces of iron/manganese secondary minerals. This study provides new insights into the heterogeneous surface complexation and retention behaviors of Tl(I) and contributes to an in-depth understanding of the environmental fate of Tl and the remediation of Tl contamination. Graphical abstract: Image, graphical abstract